(untitled) (Research, Society and Development, 2020)
Objective: Identify scientific productions about nursing interventions performed in the postoperative period of cardiac surgery during hospitalization. Method: Integrative literature review developed through the PICo strategy. The searches were performed in the databases of PUBMED, LILACS and CINAHAL, using the controlled descriptors “Cardiac Surgery/Adult or Elderly”, “Nursing Interventions” and “Hospitalization”, considering the Boolean operator “and”. Results: We identified 91 studies and 15 articles were selected and grouped into four intervention categories: Transitional nursing care in the postoperative period of cardiac surgery; Prevention of readmissions and prolongation of hospitalization; Health education before and after cardiac surgery; Anxiety and stress on patient recovery. Conclusion: This research showed the importance of nursing interventions, showing prominence in myocardial revascularization surgeries, and it is necessary to expand and develop studies in various types of cardiac interventions.